Role for Daple in non‐canonical Wnt signaling during gastric cancer invasion and metastasis. Issue 2 (23rd December 2015) - Ara, Hosne; Takagishi, Maki; Enomoto, Atsushi; Asai, Masato; Ushida, Kaori; Asai, Naoya; Shimoyama, Yoshie; Kaibuchi, Kozo; Kodera, Yasuhiro; Takahashi, Masahide
Abstract : In gastric cancer, the non‐canonical Wnt signaling pathway is activated by Wnt5a, which has a critical role in disease outcome. Previous studies have shown that Wnt5a mediates the expression of the extracellular matrix protein laminin γ2 through Rac and JNK activation to promote gastric cancer progression. However, the mechanism of this regulatory pathway has not been completely addressed. The scaffold protein Dvl is a major component of the Wnt signaling pathway. Here, we show that Dvl‐associating protein with a high frequency of leucine residues (Daple) mediates Wnt5a‐induced laminin γ2 expression. Immunohistochemical analysis showed marked expression of Daple in advanced clinical stages of gastric cancer, where it highly correlated with Wnt5a/b and laminin γ2 expression, the depth of wall invasion, and the frequency of lymph node metastasis. In cultured cancer cells, Daple depletion led to the suppression of Wnt5a‐induced Rac and JNK activation, laminin γ2 expression, and cell migration and invasion. Accordingly, Daple depletion also suppressed liver metastasis in a mouse xenograft model of gastric cancer. These results suggest that the non‐canonical Wnt signaling pathway contributes to gastric cancer progression at least in part via Daple, which provides a new therapeutic opportunity for the treatment of the disease. Abstract : In the present study, we focused on the function of Daple (Dvl‐associating protein with a high frequency of leucine residues), which we previously showed mediates the non‐canonical Wnt signaling pathway. Histological analysis on human gastric cancer tissues showed marked expression of Daple, which was correlated with Wnt5a/b and laminin γ2 expression in invasive gastric cancer. We also found that Daple mediates Wnt5a‐induced Rac and JNK activation, laminin γ2 expression, and migration and invasion in gastric cancer cells. Daple depletion suppressed liver metastasis in a mouse xenograft model of gastric cancer. Our data collectively showed that Daple is an essential protein that mediates the non‐canonical Wnt signaling pathway to regulate gastric cancer progression.